Clinical assessment and outcomes of Management of Urinary Hydatid Cyst - Asaad H. Imran1; Asif Zain Nuh (Academic Journal of Clinicians, 2022)
Urinary hydatid cyst is not uncommon in Egypt either isolated or in association with other organs’hydatid cyst in the same patient. Objective: To criticize the diagnosis and the treatment options for urinary hydatid cyst performed in the urological department at Beni Suef University Hospital. Patients and Methods: A total of 22 patients with urinary hydatid cysts who were treated in the Urology Department , Beni Suef University Hospital, were enrolled in this study during the period from December 2007 to October 2014. Treating options varies according to the size, number and the site of the cysts; these include total nephrectomy, partial nephrectomy and cyst excision for the renal hydatid, with one case treated by pyeloplasty for renal pelvic hydatid cyst. Also cyst excision was done for one patient with paravesical hydatid cyst. Results: Only 21 patients were treated surgically;Total nephrectomy performed in (7cases), partial nephrectomy in 9 cases, and4 cases with renal hydatid cyst were treated by cyst excision after instillation of a scolicidal agent, recurrence occurred in one case after one year follow up that necessitated total nephrectomy. Pyeloplasty done in one patient with renal pelvic hydatid cyst and it was uneventful. Conclusion: Hydatid cyst of the urinary system is not uncommon in Egypt, total nephrectomy, partial nephrectomy and cyst excision are the main treatment options. Lower rate of complications were reported during follow-up period